A new species of Microcaecilia (Amphibia: Gymnophiona: Siphonopidae) from the Guianan region of Brazil - Maciel, Adriano O.; Hoogmoed, Marinus S. (Zootaxa, 2013)
We describe a new species of Microcaecilia from the Guianan region of Brazil, based on a series of eight specimens from the states of Pará and Amazonas. Microcaecilia marvaleewakeae sp. nov. is very similar to M. taylori, but differs from it in having more primary annuli, more secondary grooves, and more secondary grooves that completely encircle the body. The new species also seems to have a relatively shorter and thinner head than M. taylori, but additional specimens of the new species are necessary to check this. A brief discussion of the taxonomy of M. taylori is presented.